Sleep in Renaissance Poland : Bartolomeo Berrecci's Tomb Sculpture and Its Legacy in East Central Europe - Fabiański, Marcin (Brill's Studies on Art, Art History, and Intellectual History, 2025)
Focusing on the Italian architect and sculptor Bartolomeo Berrecci, this monograph examines an important subset of his sepulchral works-recumbent statuary-and offers insights into their patronage, reception, and interpretation. Berrecci's exploration of this sculptural type predates its eventual spread beyond Italy, Spain, and Poland. Indeed, he proved so successful that well over 200 statues can still be found in present-day Poland and Lithuania, Latvia, Belarus, Ukraine and Sweden. Although he mainly produced them for Catholic clients, examples of such monuments also exist in Lutheran, Calvinist and Orthodox settings. The volume draws on a vast array of primary sources, visual, textual, and archival, and compares Berrecci's workshop to the Tuscan Quattrocento workshops of Lorenzo Ghiberti, Donatello, Perugino et al. The volume draws on a vast array of primary sources, including artworks and documents. Comparisons are made with similar compositions emanating from Tuscan Quattrocento workshops, including Lorenzo Ghiberti, Donatello and Perugino.